Pengaruh Etos Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Bima - Wisnadin Wisnadin; Kartin Aprianti (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the influence of work ethic and work discipline on the performance of Bima city population and civil registration service employees. The sample in this study was 32 ASN. Data collection techniques used were observation, questionnaires and interviews. The data analysis technique uses multiple linear regression. The results of the research show that partially and simultaneously work ethic and work discipline have a significant effect on the performance of Bima city population and civil registration service employees.